The periodic character of a class of difference equation. Issue 1 (1st February 2017) - Han, Caihong; Li, Lve
Abstract : In this paper, we study the periodic character of a class of difference equation with initial conditions being positive real numbers. We show that every positive solution of the class of difference equation global converges to a periodic solution under well-defined sufficient conditions. At last a numberical example is given to verify our theoretical results.